CLOPIDOGREL PHARMACOGENETICS - A. N. Meshkov (Столичная издательская компания, 2016)
Platelets play an important role in the pathogenesis of atherosclerosis. They are involved in atherosclerosis progression and thrombotic complications. That is why antiplatelet therapy is a necessary element of these complications prevention in patients with coronary heart disease. One of the most commonly used antiplatelet agents all over the world is clopidogrel, R2Y12-receptor blocker. It is shown that clopidogrel has insufficient effect in some patients, ie they are resistant to clopidogrel. Genetic causes of resistance to clopidogrel are considered in this review. It is shown that genetic factors related to the metabolism of clopidogrel play an important role in the resistance development. Allel variants of the gene cytochrome CYP2C19 are the main among them. The role of other genes is less studied.